ChemInform Abstract: Cytisine as a Scaffold for ortho‐Diphenylphosphinobenzenecarboxamide Ligands for Pd‐Catalyzed Asymmetric Allylic Alkylation. Issue 23 (June 2015) - Philipova, Irena; Stavrakov, Georgi; Vassilev, Nikolay; Nikolova, Rositsa; Shivachev, Boris; Dimitrov, Vladimir
Abstract Novel phosphino‐benzenecarboxamide ligands are synthesized starting from (‐)‐cytisine and applied in the Pd‐catalyzed asymmetric allylic alkylation of (E)‐1, 3‐diphenyl‐2‐propenyl acetate.